1996
DOI: 10.1182/blood.v88.8.3083.bloodjournal8883083
|View full text |Cite
|
Sign up to set email alerts
|

Frequent deletion in the methylthioadenosine phosphorylase gene in T- cell acute lymphoblastic leukemia: strategies for enzyme-targeted therapy

Abstract: Methylthioadenosine phosphorylase (MTAP), an enzyme essential for the salvage of adenine and methionine, is deficient in a variety of cancers, including acute lymphoblastic leukemia (ALL). Because the MTAP gene is located adjacent to the tumor-suppressor gene p16 on chromosome 9p21 and more than 60% of T-cell ALL (T-ALL) patients have deletion in the p16 gene, we examined the status of the MTAP gene in T-ALL patients. Quantitative polymerase chain reaction amplification of exon 8 of MTAP showed a deletion in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…MTAP deficiency was first reported in cell lines (Kamatani et al, 1982) and T-ALL (Traweek et al, 1988), but molecular explanations could not be given at that time. MTAP co-deletion has now been evidenced in many tumors with CDKN2A deletion, and a recurrent breakpoint has been observed between exons 4 and 5 (Batova et al, 1996). We found a bi-allelic deletion of MTAP in 38% of the T-ALLs studied, corresponding to 53% of cases with a CDKN2A deletion.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…MTAP deficiency was first reported in cell lines (Kamatani et al, 1982) and T-ALL (Traweek et al, 1988), but molecular explanations could not be given at that time. MTAP co-deletion has now been evidenced in many tumors with CDKN2A deletion, and a recurrent breakpoint has been observed between exons 4 and 5 (Batova et al, 1996). We found a bi-allelic deletion of MTAP in 38% of the T-ALLs studied, corresponding to 53% of cases with a CDKN2A deletion.…”
Section: Discussionmentioning
confidence: 49%
“…MTAP encodes meth-ylthioadenosine phosphorylase, a ubiquitous enzyme involved in purine and methionine salvage metabolism. It has been suggested that the loss of MTAP activity could make cancer cells more sensitive to drugs that interfere with purine metabolism (Batova et al, 1996). Therefore, in addition to the prognosis associated with CDKN2A inactivation in ALL, the extent of 9p21 deletion could be of importance for the treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is MTAP (methylthioadenosine phosphorylase), which is located close to CDKN2A and CDKN2B and is considered a functional tumor-suppressing gene that encodes a key enzyme in the catabolism of methylthioadenosine, 16,18 and the loss of microRNA-31 (hsa-miR-31), which is also located near CDKN2A, is associated with defects in the p53 pathway. 19 It has been reported that the CDKN2A/B deletion only occurs in patients with disease entities described as being aggressive in the WHO classification of cutaneous lymphomas, and so the loss of alterations are significantly associated with a poor response to treatment and poor outcomes in terms of OS and disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…2 Cells with loss of MTAP gene function become dependent on de-novo adenosine synthesis, suggesting that these tumours become highly sensitive to treatment with inhibitors of adenosine synthesis. 3 We have shown previously that allelic deletions are very frequent at 9p21 in laryngeal squamous cell carcinoma (LSCC), 4 and others have shown that MTAP allelic losses occur in 62% of oral carcinomas. 5 Loss of MTAP can be associated 6 or not associated 7 with CDKN2A loss.…”
Section: Introductionmentioning
confidence: 92%